Uma análise Vygotskiana da apropriação do conceito da simetria por aprendizes sem acuidade visual - Fernandes, Solange Hassan Ahmad Ali (2004)
The aim of this study was to investigate the processes by which blind learners appropriate mathematical concepts. In the domain of geometry, symmetry and reflection were chosen because of their strong associations with visual experiences. Within a vygotskian perspective, the research was guided by the hypothesis that, given instruments that can act as substitutes for the eye, blind learners have the same potential as their sighted counterparts to appropriate notions related to these concepts. Adopting Vygotsky's method of double stimulation, task-based interviews were realised with two subjects, one blind since birth and one who lost his sight between the ages of 4 and 15 years. The first stimulus was represented by material tools and the second offered in the form of researcher interventions. Three dimensions were chosen for analysis: the stages of geometrical thinking, intra, inter and transfigural (Piaget and Garcia, 1987); the appropriation of mathematical voices (Renshaw, 1996) and the emergence and maintenance of the zone of proximal development (Meira, 2002). Analysis of the transition between the intra and interfigural levels indicated that the evolution of meanings for symmetry and reflection in blind and sighted learners follow similar trajectories. Intrafigural aspects were appropriated more easily than the interfigural, although characteristics of the tasks and tools may well have motivated the initial preference for the intrafigural. In relation to the appropriation of the mathematical voice, the stimuli enabled the articulation of pseudoconcepts, divergences in the meanings attributed by the participants to the mathematical objects. These had an important role in promoting argumentative discourses which together with connections between knowledge learners had acquired in the past, the present situation and new knowledge (for future situations) favoured conceptual change